A Note on the Development of the Doctrine of "Forced Saving" - von Hayek, F. A. (Quarterly Journal of Economics, 1932)
Journal Article A Note on the Development of the Doctrine of "Forced Saving" Get access F. A von Hayek F. A von Hayek London School of Economics Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 47, Issue 1, November 1932, Pages 123–133, https://doi.org/10.2307/1885188 Published: 01 November 1932